THE INFLUENCE OF PRINCIPALS' LEADERSHIP MODEL ON THE AFFECTIVE COMMITMENT OF ELEMENTARY SCHOOL TEACHERS IN TEMANGGUNG DISTRICT - Rokhayati; Imron (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2024)
School success and educational success depend on the level of commitment among school staff, especially teachers. This study aims to 1) determine the leadership model, 2) determine the affective commitment of teachers, and 3) determine the influence of the principal's leadership model on the affective commitment of teachers in elementary schools in Temanggung District. This research was conducted with a descriptive quantitative approach. The population in this study were elementary school teachers in Temanggung Regency, totaling 142 teachers from 9 schools. The sampling technique used in this study was probability sampling, which included 50% of the total population. Thus, the number of samples in this study was 71 teachers. The data collection technique used in this study was a questionnaire. Data analysis is used to analyze descriptive statistics and linear regression. The results of this study showed: 1) the leadership model of principals in elementary schools in Temanggung Sub district from a total of 9 schools found two schools with autocratic leadership and four schools with democratic leadership models, as well as three schools with laissez-faire (free control) leadership models; 2) Teachers' affective commitment is in a good category, this is evidenced by the percentage distribution of 3) There is a positive and significant influence between the principal's leadership model on the affective commitment of teachers, the autocratic leadership model influences the affective commitment of teachers by 24 2%, the free control/laissez-faire leadership model with details of the effective contribution of 64.9%, which gives influence to the affective commitment of teachers is a democratic leadership model with an effective contribution of 49.2%.